A Needs Assessment of Breast Pathology Services in Sub-Saharan Africa. - Omoyiola, Oluwatosin; Gilliland, Jaime L.; Betiku, Omolade; Nkya, Gilbert; Couto Fernandes, Fabiola; Tacula, Neybi Stella; Carrilho, Carla; Pallangyo, Angela Elisha; Adegoke, Omolade; Edelweiss, Marcia; Ng, Dianna L. (Archives of Pathology & Laboratory Medicine, 2026)
Context.--High-quality breast pathology services are a cornerstone to rendering accurate and timely diagnostic reports essential for breast cancer management. Objective.--To perform a qualitative needs assessment of breast pathology services across several large referral hospitals in sub-Saharan Africa to better understand the challenges in providing optimal pathology services. Design.--We conducted semi-structured interviews with key stakeholders involved in breast cancer care, including pathologists, radiologists, oncologists, and surgeons from Nigeria, Tanzania, and Mozambique. All interviews were conducted by a breast pathologist with subspecialty training based in the United States. Interviews explored the current gaps in pathology services. Responses were recorded, key points transcribed and coded by using thematic content analysis, and major themes were identified. Results.--Individual interviews were conducted with a total of 6 pathologists, 3 radiologists, 2 oncologists, and 6 surgeons. Major themes identified included pathology reporting practices, laboratory workflow, pathology infrastructure, and challenges in communication between clinical specialties. Participants expressed a desire for more consistent and structured reports, including standardization of essential information and the use of synoptic templates. Conclusions.--Addressing gaps in breast cancer pathology services in sub-Saharan Africa will require a multifaceted approach. Critical areas to focus on include interventions to strengthen laboratory infrastructure, increasing availability of context-tailored subspecialty training, standardizing laboratory protocols and specimen reporting, and establishing communication channels between clinical specialties. Building pathology capacity in sub-Saharan Africa will improve not only diagnosis but also treatment planning and patient outcomes.